Attitudes of Smartphone User SMP and its Implications in Guidance and Counseling - Zaharani Zaharani; Zikra Zikra (Universitas Negeri Padang, 2021)
This research is motivated by the phenomenon of students trying to open pornographic sites via smartphones, students seeing how expensive smartphones are owned as a measure of social status, and there are students who are not happy when the use of smartphones is limited by teachers. This study aims to: (1) describe the attitudes of students using smartphones from the cognitive components, (2) to describe the attitudes of students using smartphone users from the affective component, and (3) to describe the attitudes of students using smartphone users from the conative component. This research is a type of quantitative research with descriptive methods. The subjects of this study were all students of SMPN 4 Lembah Melintang West Pasaman Regency who were actively registered in the 2019/2020 school year. The number of subjects was 32 students with the criteria of students using smartphones. Data were analyzed using descriptive statistical techniques. The results of the study revealed that (1) the attitudes of smartphone users in terms of cognitive components were in the low category, (2) the attitudes of smartphone users in terms of the affective components were in the medium category, and (3) the attitudes of smartphone users in terms of the components. conative is in the low categoryBased on the research findings, it is suggested that BK teachers or school counselors be able to provide guidance and counseling services, information services, individual counseling services, group guidance services to students, in order to help and minimize students falling into the wrong attitude towards smartphone use.